Versoening in Suid-Afrika na die Waarheids- en-Versoeningskommissie: die rol van die NG Kerk - Meiring, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
The question is frequently debated whether the South African Truth and Reconciliation Commission (TRC) facilitated or hindered reconciliation in South Africa. The author, who served on the TRC, discusses various answers to the question, quoting from the experiences and views of victims, perpetrators, as well as the general public in this regard. Turning to the challenges to the faith communities contained inter alia in the Final Report of the TRC, he mentions five specific challenges that, while being important to all churches, are of specific relevance to the Dutch Reformed Church (NG Kerk), a denomination that over many years provided theological and practical support to the system of apartheid.